BS EN 4165-017. Aerospace series. Connectors, electrical, rectangular, modular. Operating temperature 175 °C continuous. Part 017. Blank chimney for accessory (1 per module cavity). Product standard (10th December 2021) - British Standards Institution,
No abstract available